Quantifying the spatial extent of the corollary discharge benefit to transsaccadic visual perception - Jayet Bray, Laurence C.; Bansal, Sonia; Joiner, Wilsaan M. (Journal of neurophysiology, 2016)
Extraretinal information, such as corollary discharge (CD), is hypothesized to help compensate for saccade-induced visual input disruptions. However, support for this hypothesis is largely for one-dimensional transsaccadic visual changes, with little comprehensive information on the spatial characteristics. Here we systematically mapped the two-dimensional extent of this compensation by quantifying the insensitivity to different displacement metrics. Human subjects made saccades to targets positioned at different amplitudes (4° or 8°) and directions (rightward, oblique, or upward). After the saccade the initial target disappeared and, after a blank period, reappeared at a shifted location—a collinear, diagonal, or orthogonal displacement. Subjects reported the perceived shift direction, and we determined the displacement detection based on the perceptual judgments. The two-dimensional insensitivity fields resulting from the perceptual thresholds had spatial features similar to the saccadic eye movement variability: 1) scaled with movement amplitude, 2) oriented (less sensitive to the change) along the saccade vector, and 3) approximately constant in shape when normalized by movement amplitude. In addition, comparing the postsaccadic perceptual estimate of the presaccadic target location to that based solely on the postsaccade visual error showed that overall the perceptual estimate was approximately 50% more accurate and 35% less variable than estimates based solely on this visual information. However, this relationship was not uniform: The benefit of extraretinal information was observed largely for displacements with a component parallel to the saccade vector. These results suggest a graded use of extraretinal information when forming the postsaccadic perceptual evaluation of transsaccadic environmental changes.